2015
DOI: 10.1186/s40510-015-0096-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two maxillary protraction protocols: tooth-borne versus bone-anchored protraction facemask treatment

Abstract: BackgroundProtraction facemask has been advocated for treatment of class III malocclusion with maxillary deficiency. Studies using tooth-borne rapid palatal expansion (RPE) appliance as anchorage have experienced side effects such as forward movement of the maxillary molars, excessive proclination of the maxillary incisors, and an increase in lower face height. A new Hybrid Hyrax bone-anchored RPE appliance claimed to minimize the side effects of maxillary expansion and protraction. A retrospective study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
86
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 35 publications
13
86
3
4
Order By: Relevance
“…Several clinical studies and case reports with different treatment protocols have combined this hybrid hyrax with facemasks for maxillary protraction in Class III patients [48,[54][55][56]69]. Some of these studies [54][55][56] demonstrated advancement of the maxillary complex by statistically significant amounts which, due to the extraoral forces from facemasks, were larger than reported in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…Several clinical studies and case reports with different treatment protocols have combined this hybrid hyrax with facemasks for maxillary protraction in Class III patients [48,[54][55][56]69]. Some of these studies [54][55][56] demonstrated advancement of the maxillary complex by statistically significant amounts which, due to the extraoral forces from facemasks, were larger than reported in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…Recently, Ngan et al had reported that in non-cleft class III individuals, the hybrid HYRAX bone-borne expansion device along with maxillary protraction yielded desirable sagittal skeletal change with minimal dental side effects [41]. Also Lin et al had concluded that in non-cleft individuals bone-borne maxillary expansion produced greater transverse orthopedic effects [42].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, comparison of the long-term results of early FM therapy and BAMP, when available, will be very interesting. A number of treatment protocols using a maxillary expansion and protraction reported favorable short-term results in non-cleft subjects of 9-12 years old in terms of A point advancement [7,[25][26][27][28][29]. Most of the studies were retrospective, with relatively small sample size or without untreated controls.…”
Section: Discussionmentioning
confidence: 99%
“…Less dental compensations are demonstrated when a facemask used in combination with a Hybrid Hyrax, a rapid palatal expansion appliance which is both tooth-and bone-borne. [7]. Protocols of maxillary expansion and protraction, such as the Alternate Rapid maxillary Expansions and Constrictions protocol(Alt-RAMEC), proposed by Liou et al, showed favorable skeletal results up to 17 to 21 years of age in some patient, but with evident dental compensation [8,9].…”
Section: Introductionmentioning
confidence: 99%